Tindakan Penyadapan Ditinjau dari Perspektif Hukum Pidana - Hwian Christianto (Jurnal Hukum PRIORIS, 2016)
Regulation of interception or wiretapping activity is always pro-and contra in legislation process or into its application. The human rights-violation and law supremacy issues are often exclaimed as an un-cultivated Indonesians to interception/wiretapping activity. Based on the essential implication, interception/wiretapping activity basically has two main ideas which are considered as subtracting the human rights anyway. The implication is very attracting because it is strongly related with person’s privacy and it has to face wider business of the public. This interception/wiretapping might not be applied carelessly of course, but on another hand, it has to see the particular limits. Finally, the interception/wiretapping regulation ought to be notice, so that there will be no unpleasant ‘boomerang’ effect for human rights protection.Keyword: interception, human rights, protection